2014
DOI: 10.1002/rnj.137
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Anxiety Levels of Parents with Disabled Children

Abstract: The development and implementation of alternative support systems for of parents with disabled children would be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The results of this study also showed that despite reporting low social and emotional supports from friends, mothers of children with special needs were not significantly different from the mothers of children without special needs in terms of perceived social support. This finding is consistent with the results of some studies (34,35); however other studies have shown that the extent of perceived emotional support in parents of children with special needs can be effective in reducing the symptoms of depression, anxiety, and stress in them (30). Having a satisfactory perception of emotional support from others plays an important role in managing and fulfilling maternal responsibilities.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study also showed that despite reporting low social and emotional supports from friends, mothers of children with special needs were not significantly different from the mothers of children without special needs in terms of perceived social support. This finding is consistent with the results of some studies (34,35); however other studies have shown that the extent of perceived emotional support in parents of children with special needs can be effective in reducing the symptoms of depression, anxiety, and stress in them (30). Having a satisfactory perception of emotional support from others plays an important role in managing and fulfilling maternal responsibilities.…”
Section: Discussionsupporting
confidence: 91%
“…It was found that trait anxiety scores decreased as the age of the parents increased (56 years and over). Özyazıcıoğlu and Buran (2014;228) found a negative relationship between state anxiety levels and age in their study on families with mentally retarded children. When the literature is examined, families worry about who will take care of their children and what will happen to them as the age of their mentally retarded child gets older or after he/she passes away (Kaytez et al, 2014;208).…”
Section: Discussionmentioning
confidence: 96%
“…Combined, these challenges contribute to family fragility, decreased well-being, and poorer quality of life for people with ASD and their families. Information seeking as a mechanism for increased agency and coping has been well recognized in the LIS literature (Chatman 1996;Harris et al 2001;Savolainen 1995;Wilson 2000) and, though less prevalent, particularly observed in information behavior studies of parents who have children with significant health concerns and disabilities (Al-Daihani and Al-Ateeqi 2015;Gibson 2014;Jackson et al 2008;Mackintosh, Myers, and Goin-Kochel 2005;Özyazıcıoğlu and Buran 2014).…”
Section: Introductionmentioning
confidence: 99%